Coronavirus disease vaccine linked menstrual changes: mobile application study - Sung Eun Kim; Joseph J. Noh; Yoo-Young Lee (Obstetrics & Gynecology Science)
Objective Since coronavirus disease 2019 (COVID-19) vaccination began, abnormal uterine bleeding (AUB) has occurred at a high rate. This study assessed the association between COVID-19 vaccination and AUB. Methods In this retrospective cohort study, we analyzed mobile application data on menstrual cycles to investigate differences in the prevalence, duration, and amount of intermenstrual bleeding (IMB) after COVID-19 vaccination. We also analyzed the duration of menstruation, menstrual cycle length, and associated symptoms after the COVID-19 vaccination. Additionally, we investigated the prevalence of IMB according to the vaccine type. Results After vaccination, IMB prevalence increased to 3.35% (odds ratio [OR], 1.61; 95% confidence interval [CI], 1.46–1.76; P<0.0001) and IMB duration increased by 0.43 days (95% CI, 0.25–0.60; P<0.0001). The proportion of respondents whose amount of IMB was heavier than regular menstruation increased (OR, 2.96; 95% CI, 1.47–5.93; P=0.002). Menstrual duration decreased by −0.01 days (95% CI, −0.023 to 0.003; P=0.114), and menstrual cycle length increased by 1.39 days (95% CI, 1.30–1.48; P<0.0001). The proportion of participants who answered that there was a difference in menstruation amount increased (OR, 1.52; 95% CI, 1.41–1.64; P<0.0001). The prevalence of IMB increased regardless of the vaccine type. Conclusion There were statistically significant differences in the prevalence, duration and amount of IMB, menstrual duration, menstrual cycle length, and menstrual amount after COVID-19 vaccination. However, these values were not clinically meaningful and could be regarded as within the normal menstruation range.